Optimization of Literacy Clinic Empowerment: An Efforts to Improve Teachers' Ability in Dealing with High Grade Students Who Have Difficulties in Reading - Nurjamin, Asep; Nurwahidah, Lina Siti; Nugraha, Fajar (Jurnal Abdimas, 2024)
One of the learning problems experienced by high school teachers is the difficulty of teaching students who have difficulty reading. This problem often makes teachers helpless. Therefore, a training program entitled "Optimizing the Empowerment of Literacy Clinics" was carried out for two days on June 4-5, 2024, which was attended by eighty-two fifth-grade high school teachers. The main objective of this training is to empower teachers in providing support and guidance to students who have difficulty reading through "literacy clinics", so that they are able to provide appropriate and sustainable interventions. The training materials are very necessary and effective in improving the reading skills of high school students who have difficulty reading. The success of the training can be seen from the high attendance of participants, good absorption of the material, and the preparation of logical and measurable follow-up plans by all participants. The results of the program evaluation showed significant achievement of objectives. Further recommendations include in-depth evaluation, further training, external collaboration, and dissemination of best practices to increase the impact of the program in the future.